IMPACT OF BMI ON THE SEVERITY OF GERD SYMPTOMS, A DESCRIPTIVE STUDY - Muhammad Younas; Syed Hira Hassan; Fida Muhammad Khan; Salman Afridi; Asif Khan; Shafqat Ali; Aafaq Ahmad; Nowshad Khan (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Gastro esophageal reflux disease (GERD) is a common gastrointestinal disease that has worldwide prevalence. It is characterized by the backflow of gastric contents into the esophagus, which typically causes unpleasant symptoms in the form of water brash, retrosternal burning sensation and dysphagia.Objective: The aim of this study to understand the association between BMI and GERD symptoms.Study Design: Descriptive StudyDuration and Place of Study: The study was carried out between February 2023 and November 2023 at the Department of Gastroenterology, Hayatabad Medical Complex, Peshawar, Pakistan.Material and Methods: The study involved a cohort of 185 participants who were diagnosed with GERD. Essential demographic information was collected and BMI was recorded. GERD symptoms in patients with normal BMI and raised BMI as per WHO classification, were compared.Results: The study included 185 patients, with a nearly equal proportion of male (48.65%) and females (51.35%). Patients ranged in age from 18 to 30 years (24.32%), 31 to 45 years (32.43%), 46 to 60 years (27.03%), and 61 years or more (16.22%). Severe symptoms were reported by 4.4% patients with normal BMI, 38.7% who were overweight and 23.6% patients who were obese.Conclusion: The high rate of occurrence of severe symptoms in overweight and obese patients shows increase severity with raised BMI and emphasizes the need of weight control in GERD treatment.